Upaya Peningkatkan Hasil Belajar Siswa melalui Metode Pembelajaran Cooperative Learning pada Materi Pelajaran Sistem Pencernaan Manusia di Kelas VIII-5 MTs Negeri 2 Kota Bima - Salmi (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
Preliminary observations showed that students' understanding of the subject matter of the Human Digestive System was still low. The low understanding of students is caused by teacher and student factors. In this regard, this study aims to determine the increase in student learning outcomes on the subject matter of the Human Digestive System using the Cooperative Learning method. This research was conducted through three stages, namely planning, implementation, and evaluation and reflection using two cycles. The results of the research on students' understanding of the subject matter of the Human Digestive System in class VIII-5 students of MTsN 2 Kota Bima experienced an increase, namely the results of the evaluation of teacher activity cycle I compared to classical learning, the moderate category increased to the capable category. The results of evaluating the activities of students in cycle II were almost 92% in the very capable category. The number of students who passed in cycle I and cycle II also continued to increase so that it can be said that they have met the completeness target. From the implementation of these 2 cycles, it can be concluded that learning using the cooperative learning method is able to increase understanding of the subject matter of the Human Digestive System.